U.S. Government engagement in support of global disease surveillance - Gay Cyril G; Cole Kenneth; Chapman Leonard W; Carroll Dennis; Arthur Ray R; Annelli Joseph F; López Leana M; Katz Rebecca L; Lowe Daniel L; Resnick Gary; Russell Kevin L (BMC, 2010)
Abstract Global cooperation is essential for coordinated planning and response to public health emergencies, as well as for building sufficient capacity around the world to detect, assess and respond to health events. The United States is committed to, and actively engaged in, supporting disease surveillance capacity building around the world. We recognize that there are many agencies involved in this effort, which can become confusing to partner countries and other public health entities. This paper aims to describe the agencies and offices working directly on global disease surveillance capacity building in order to clarify the United States Government interagency efforts in this space.